Modeling of melting and resolidification of equiaxed microstructures in a temperature gradient. (1st July 2018) - Zhang, Qingyu; Fang, Hui; Xue, Hua; Tang, Qianyu; Pan, Shiyan; Rettenmayr, Markus; Zhu, Mingfang
Abstract: Melting and resolidification in a temperature gradient are simulated using a cellular automaton (CA) model for an Al–Cu alloy with initially equiaxed microstructures. The simulations exhibit liquid pockets appearing at grain boundaries and in the grain interior, as well as their coalescence and migration towards the high temperature direction due to temperature gradient zone melting. The simulated microstructures agree well with experimental micrographs. The liquid fraction and solute concentration distributions throughout the mushy zone are quantified; they compare reasonably well with analytical predictions. The simulations provide insight into the complex interactions among temperature gradient and solute (re)distribution during melting/resolidification. Graphical abstract: Unlabelled Image